Verbal Treasures of Pavlenko Larysa Petrivna (Linguostylistic Studies, 2018)
The article describes the basic biographical information about L.P. Pavlenko, a well-known linguist. The author analyzes the scholar's major scientific achievements with the focus on the research papers regarding the history of language, onomasiology and linguistic personolog.
Keywords: L. P. Pavlenko; history of language; onomasyology and linguistic personology